Excellent response to therapeutic plasma exchange in myasthenia gravis patients irrespective of antibody status. Issue 4 (19th February 2019) - Usmani, Amena; Kwan, Laura; Wahib‐Khalil, Dina; Trivedi, Jaya; Nations, Sharon; Sarode, Ravi
Abstract: Introduction: The primary objective of this study was to assess response to plasma exchange (PLEX) in myasthenia gravis (MG) patients with and without autoantibodies (Ab) to acetylcholine receptor (AChR) or muscle‐specific kinase (MuSK). Analysis was also done to determine if correlation existed between sex, early or late onset MG, thymoma, or thymectomy and response to PLEX. Materials and Methods: Data was analyzed on 58 consecutive MG patients treated with PLEX. Responses were categorized as complete response, clinical improvement requiring maintenance PLEX, or no/minimal response to PLEX. Results: Eighty‐eight percent (51/58) of patients were Ab‐positive; 44 had AChR and 7 had MuSK Ab. Complete response was seen in 26 patients (24 Ab+), 24 remain on maintenance PLEX (19 Ab+), and 2 had no/minimal response (both AChR Ab+). Ab status ( P  = 0.43), AChR Ab ( P  = 0.10), MuSK Ab ( P  = 0.45), early onset MG ( P  = 0.63), thymoma ( P  = 0.46), and thymectomy ( P  = 0.16) were not significantly associated with outcome. Patient sex did show significant association with outcome ( P  = 0.01), with men more likely to have complete response and women more likely to require maintenance. Late onset MG is significantly associated with higher likelihood of complete response ( P  = 0.03). Antibody titers declined after PLEX in 83% of patients with complete response, in whom pre‐ and post‐PLEX titers were available ( n  = 6). Conclusions: In conclusion, our study showed 96% response rate to PLEX in MG; however, only patient gender and late onset MG were significantly associated with treatment response.